Predictive Value of Blood Ammonia in the Prognosis of Acute Liver Failure Evaluated by Receiver Operating Characteristic Curves - Lei Li; Peng Liu; Ke Li; Fang Lin; Cheng-Cheng Ji; Yong-Gang Wang; Biao Xu; Jin-Song Mu; Yue-Su Zhou (Turkish Journal of Gastroenterology, 2021)
Background: To investigate the predictive value of blood ammonia (BLA) quantification in the prognosis of acute liver failure (ALF).Methods: Seventy-one patients with ALF were enrolled and BLA concentration was measured in all patients. After following up for 28 days, patients were divided into two groups: the surviving group (n = 21) and the deceased group (n = 50). An independent-samples t-test was used to compare BLA concentrations between the two groups, and receiver operating characteristic curves were used to evaluate the predictive value of BLA in the prognosis of ALF. A fourfold table analysis was performed with the determined BLA cutoff value.Results: The average concentration of BLA in the deceased group was significantly higher compared with the surviving group (144.50 µmol/L vs. 106 µmol/L, respectively; P = .035). The cutoff BLA concentration for a good ALF prognosis was 122.5 µmol/L. The area under the curve was 0.659. Both the sensitivity and specificity were >0.6. The 95% CIs for sensitivity and specificity were 0.452-0.733 and 0.477-0.878, respectively. The fourfold table analysis revealed a positive predictive value of 83.3%, a negative predictive value of 42.9%, a misdiagnosis rate of 28.6%, and an accuracy of 63.4%.Conclusion: With a cutoff BLA concentration of 122.5 µmol/L, the prognosis of ALF could be predicted with high sensitivity and specificity, a positive predictive value, a low misdiagnosis rate, and good accuracy.Cite this article as: Li L, Liu P, Li K, et al. Predictive value of blood ammonia in the prognosis of acute liver failure evaluated by receiver operating characteristic curves. Turk J Gastroenterol. 2021; 32(2): 164-168.